2019
DOI: 10.1038/s41598-019-54404-7
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial on clinical performances and biocompatibility of four high-flux hemodialyzers in two mode treatments: hemodialysis vs post dilution hemodiafiltration

Abstract: This prospective multicenter randomized comparative cross-over trial aimed at evaluating the influence of hemodialysis vs post-dilution hemodiafiltration with high-flux dialyzers in solute clearance and biocompatibility profile. 32 patients were sequentially dialyzed with Leoceed-21HX, Polypure-22S+, Rexsys-27H and VIE-21A. Primary outcome was β2-microglobulin removal. Secondary outcomes were (i) extraction of other uremic solutes (ii) parameters of inflammation and nutrition and (iii) comparative quantificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…Many studies on high-volume OL-HDF have demonstrated a superior removal of higher molecular weight substances-such as b2MG, myoglobin, free immunoglobulin light chains Kappa, β-trace protein, orosomucoid, indoxyl-sulfate, and p-cresyl-sulfate-as compared to HD. 7,8 Higher fluid substitution rates are associated with higher b2MG clearances post-HDF therapies. 9 The maximum benefit of OL-HDF on middle molecule removal may be achieved with 24 L substitution volume per 4-h treatment.…”
Section: Middle Molecules and Protein Bound Uremic Toxinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies on high-volume OL-HDF have demonstrated a superior removal of higher molecular weight substances-such as b2MG, myoglobin, free immunoglobulin light chains Kappa, β-trace protein, orosomucoid, indoxyl-sulfate, and p-cresyl-sulfate-as compared to HD. 7,8 Higher fluid substitution rates are associated with higher b2MG clearances post-HDF therapies. 9 The maximum benefit of OL-HDF on middle molecule removal may be achieved with 24 L substitution volume per 4-h treatment.…”
Section: Middle Molecules and Protein Bound Uremic Toxinsmentioning
confidence: 99%
“…Where some studies suggest no differences in HRQoL scores between HDF and HD patients, [7][8][9][10]46 conversely, others have demonstrated a beneficial effect of HDF on HRQOL, including social, physical, and professional domains in association with fewer episodes of hypotension, cramps, itching, fatigue, joint pain, and stiffness. 8,[12][13][14] However, this evidence is limited in terms of sample size and follow-up.…”
Section: Patient Reported Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…-Calculation of FLC post-dialysis concentration corrected for net ultrafiltration with the following equation: 4 ,13 Fpost.c = -Cumulative albumin loss was measured by the following equations: 12,14 Cumulative dialysate Albumin (gm) = Albumin ½ hr + Albumin 1 st hr +Albumin 3 rd hr + Albumin 4 th hr -Albumin lost over first half or 1 st hour was measured by equation "A".…”
Section: Rr =mentioning
confidence: 99%
“…11,12 Regular use of ultrapure dialysis fluid, as required for online HDF contributes to improved hemocompatibility of the dialysis system and reduces inflammation reactions. 13,14 Advances in technology, have resulted in online HDF becoming as simple, safe and costeffective as regular hemodialysis. [15][16][17] Successful clinical implementation of online HDF took less than 3 days in naïve centers, as recently shown in a large prospective study.…”
Section: Introduction: Why Hemodiafiltration Is Different From Contem...mentioning
confidence: 99%